Tien eeue leksikografie: Van woordelys tot woordeboek - Wyk, Wouter C. van (Hervormde teologiese studies, 1985)
Ten centuries of lexicography: From vocabulary list to dictionary The aim of the article is to illuminate the development in the lexicography of Biblical Hebrew through ten centuries from the first vocabularly list to a dictionary based on linguistic, comparative Semitic and encyclopedic principles. The writer treats several stages through the Middle Ages, the Reformation period, the Enlightenment and the Twentieth century up to a contemporary project of South African scholars working on a new Semantic Hebrew 'wordbook'. The conclusion in the article is that the nature of a specific dictionary or vocabularly list, for example philological, theological or linguistic, serves particular, legitimate needs.